The effect of a denture cleanser on the properties of a flexible thermoplastic resin / Hazem Mofreh Altarawneh - Hazem Mofreh, Altarawneh (2019)
Purpose: This in-vitro study was carried out to evaluate the effect of a denture cleanser on the color stability, surface roughness, and the flexural modulus of a flexible polyamide thermoplastic denture base material, following immersion in a commercially available neutral peroxide enzymatic denture cleanser. Materials and methods: Sixty (60) rectangular specimens (64mm x 10mm x 3.3mm) of polyamide thermoplastic denture base material (Vertex™ ThermoSens) were prepared and immersed in distilled water (n=25) as control, and a denture cleanser (Polident 3 min™), simulating 180 days of usage (n=25), 10 specimens were not immersed in any solution for baseline measurements. Color measurements (∆E) were obtained using Spectrophotometer. The surface roughness (Ra) was determined using an optical 3-dimensional (3D) surface analyzer. Three-point bending test executed using a universal testing machine to measure the flexural modulus∆E values were submitted to statistical analysis by means of One-sample test, then the Paired sample test was used to compare the color parameters (L*, a*, b*). The Ra values were analyzed using the Paired sample test. The flexural modulus values were submitted to One-way ANOVA test. All the statistics were done at a significant level of P=0.05 with the aid of the statistical program SPSS 20.0 (SPSS Inc., Chicago, IL,USA). Results: Following the immersion in the denture cleanser, the mean of the color changes (∆E) (0.75±0.47) showed statistically significant difference (p<0.05) compared to the control group (0.27±0.21), however, it was classified as slight (0.5-1.5) when quantified by the National Bureau of Standards (NBS). There was a significant increase (p<0.05) in the surface roughness (Ra) was detected after the immersion. However, there was no significant difference in the flexural modulus (p<0.05) between the control, the test and non-immersed groups. Conclusion: The use of the neutral peroxide enzymatic vi denture cleanser Polident 3 min™ significantly increases the surface roughness of the polyamide thermoplastic denture base material (Vertex™ ThermoSens), however, the color changes were within the clinically accepted range, and the changes in the flexural modulus of the material were not significant.